Effects of land use on benthic macroinvertebrate assemblages at three rivers in Endau catchment area, Kluang, Johor, Malaysia - Aweng Eh Rak; Ismid Said; Maketab Mohamed (2011)
Study was conducted for six times from November 2008 to June 2010 to determine the effect of land use on benthic macroinvertebrate assemblages in Mengkibol, Madek and Dengar rivers. Eight stations were selected which two stations from each river except Dengar which has two sampling reach comprised of four stations. A 500 meter reach of the stream was selected for each sampling site. One sampling reach comprises of two sampling stations where one station is located at the upper reach, while the other station is situated at the lower reach. Surber Net measuring 500 micron mesh size combined with a rectangular quadrat of 30 cm x 30 cm (0.09 m2) was used to sample macroinvertebrates. The results showed that un-disturbed river has complete sensitive taxa namely Ephemeroptera, Plecoptera and Trichoptera (EPT). Mean while, there were only two sensitive taxa namely Ephemeroptera and Trichoptera were found in the river which flows through palm oil plantation. Similar scenario was found in the river which flows through logging area where there were also two sensitive taxa namely Ephemeroptera and Trichoptera found in this river. In addition, the results obtained for urban river was the other way round where there was an absent of all three sensitive taxa (EPT) in the river which flows through urban area. Most of the macroinvertebrate taxa that were found in this station are pollution resistant taxa comprised Diptera, Odonata, Mesogastropoda, Basommatophora, Hirudinea and Haplotaxida. The results can be use as a biological indicator for river water quality assessment.